Клинкова зброя з Середнього Подністров’я і військова справа Болгарської держави в ІХ – першій половині Х ст. - Калініченко, Віталій (Чернівці, Чернівецький університет, 2017)
This article analyzes objects bladed weapons, which comes from the territory of the Middle Dniester and dates from the IX-th – first half of the X-th century. Among them, one and a saber and 2 fragments that belong to sabers so-called “bulgarian” type. This type of bladed weapons was distributed in the Carpathian-Balkan region and is considered a clear indicator of the military culture of the First Bulgarian State in the IX – first half of the X-th century. The author holds characteristic relationships and mutual medieval population of Potyssya, territory of the Middle Dniester, the Danube and the Black Sea region in the set up period. V. Yotov believes that this type of sabers spread in First Bulgarian state after the relocation of the khazars and bulgarians from the Khazar Khanate as a result of the сivil war in the latest at the beginning of the ІХ-th century. We believe that this type of sabers could enter the territory of the First Bulgarian state earlier, particularly in the VIII century, аnd after already spread to the boundaries of the territory of the Middle Dniester in connection with bulgarian expansion to the territory of the Tysa-Dniester river interfluve in the early IX century.The findings of this type of sabers allow other positions look at the history of the medieval population of the Middle Dniester and analyze complex military-political processes taking place in the defined region in the IX- th – first half of the X-th century.
Bladed weapons from territory of Middle Dniester and military science of the Bulgarian state in the IX – first half of the X century
Keywords: Середнє Подністров’я; Перша Болгарська держава; військова справа; клинкове озброєння; шабля